2012
DOI: 10.1242/dev.085597
|View full text |Cite
|
Sign up to set email alerts
|

Differential requirements for β-catenin during mouse development

Abstract: SUMMARYEmbryogenesis relies on the precise interplay of signaling cascades to activate tissue-specific differentiation programs. An important player in these morphogenetic processes is -catenin, which is a central component of adherens junctions and canonical Wnt signaling. Lack of -catenin is lethal before gastrulation, but mice heterozygous for -catenin (Ctnnb1) develop as wild type. Here, we confine -catenin amounts below the heterozygous expression level to study the functional consequences for develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…Consistent with other recent studies (del Valle et al, 2013;Faunes et al, 2013;Rudloff and Kemler, 2012), however, our data do not preclude a non-transcriptional role for β-catenin in the maintenance of pluripotency in vitro.…”
Section: Research Articlesupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with other recent studies (del Valle et al, 2013;Faunes et al, 2013;Rudloff and Kemler, 2012), however, our data do not preclude a non-transcriptional role for β-catenin in the maintenance of pluripotency in vitro.…”
Section: Research Articlesupporting
confidence: 93%
“…We show here that zygotic Porcn mutants fail to gastrulate and remain in an Oct3/4 + Otx2 + epiblast-like state, similar to Porcn epiblast-specific mutants. This not only phenocopies Wnt3 mutants (Liu et al, 1999), but also a group of 'canonical Wnt null' phenotypes, such as Wls (Fu et al, 2009), Mesd1 (Mesdc1 -Mouse Genome Informatics) (Hsieh et al, 2003), Lrp5/6 compound mutants (Kelly et al, 2004), and epiblast-specific Ctnnb1 mutants (Rudloff and Kemler, 2012). Strikingly, the phenotype of the downstream effector Ctnnb1 differs slightly (Haegel et al, 1995;Huelsken et al, 2000;Morkel et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…␤-catenin flox/Ϫ cells respond to Wnt3a stimulation with the up-regulation of the canonical Wnt signaling targets Axin2, Cdx1, and brachyury (T) within 4 h after Wnt3a supplementation (25), and SR1-Cre-ERT2 are similarly Wnt3a responsive. 2 Interestingly, we could not observe a significant increase in the protein levels of chromatin-bound ␤-catenin in mES cells after Wnt3a, LiCl, or GSK3a inhibitor treatments (supplemental Fig.…”
Section: ␤-Catenin Chromatin Interactome In Mouse Embryonic Stem Cellsmentioning
confidence: 99%
“…Given the fundamental requirement for β-catenin in multicellular forms of life (Dickinson et al, 2011), as well as the presence of β-catenin (CTNNB1) in the mouse oocyte and the early activation of Ctnnb1 in the 2-cell embryo (Bauer and Willert, 2012;de Vries et al, 2004;Valenta et al, 2012), it was a surprise to find that there is no phenotypic effect in Ctnnb1 null offspring of Ctnnb1 +/− B6.129 mice until ∼5.5 days post coitum (dpc), when the well-known role of CTNNB1 in the Wnt signaling pathway becomes essential for gastrulation (Haegel et al, 1995;Huelsken et al, 2000;Rudloff and Kemler, 2012). These authors suggested that either plakoglobin, a closely related protein, or maternally contributed CTNNB1 is able to support preimplantation embryonic development.…”
Section: Introductionmentioning
confidence: 99%